The Stydying of the Notion of Language Economy in Linguistics - Azamatjon, Artikov; Rasulov , Zubaydullo Izomovich (Miasto Przyszłości, 2023)
The article deals with the development of the concept of linguistic economy in linguistic literature. In connection with this concept, a corresponding terminology has arisen. It has changed since ancient times and was developed in the 19th-20th centuries on the basis of various languages. Thus, economy as one of the principles of the functioning and development of the language is studied at its different levels, where the means of expressing economy and the possibilities of its manifestation in the context of a general statement are established.